Mechanical Stress as the Common Denominator between Chronic Inflammation, Cancer, and Alzheimer’s Disease - Levy Nogueira, Marcel; da Veiga Moreira, Jorgelindo; Baronzio, Gian Franco; Dubois, Bruno; Steyaert, Jean-Marc; Schwartz, Laurent (Frontiers in Oncology, 2015)
The pathogenesis of common diseases such as Alzheimer’s disease (AD) and cancer are currently poorly understood. Inflammation is a common risk factor for cancer and AD. Recent data, provided by our group and from others, demonstrate that increased pressure and inflammation are synonymous. There is a continuous increase in pressure from inflammation to fibrosis and then cancer. This in line with the numerous papers reporting high interstitial pressure in cancer. But most authors focus on the role of pressure in the lack of delivery of chemotherapy in the center of the tumor. Pressure may also be a key factor in carcinogenesis. Increased pressure is responsible for oncogene activation and cytokine secretion. Accumulation of mechanical stress plays a key role in the development of diseases of old age such as cardiomyopathy, atherosclerosis and osteoarthritis. Growing evidence suggest also a possible link between mechanical stress in the pathogenesis of AD. The aim of this review is to describe environmental and endogenous mechanical factors possibly playing a pivotal role in the mechanism of chronic inflammation, AD and cancer.